2016
DOI: 10.3346/jkms.2016.31.10.1553
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Antimicrobial Stewardship Programs in Korea, 2015

Abstract: The study was conducted to evaluate the Antibiotic Stewardship Program (ASP) in Korean hospitals compared with the previous two surveys in 2006 and 2012. The information on ASPs was collected through an online-based survey sent by e-mail to 192 infectious diseases specialists in 101 Korean hospitals in September 2015.Fifty-four hospitals (53.5%, 54/101) responded to the online survey. One infectious diseases specialist was employed in 30 (55.6%) of the 54 hospitals, and they were in charge of ASPs in hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…As these infections are largely viral and self-limiting, antibiotics offer little benefit for these conditions (56). Globally, concerted efforts targeting both clinicians and the public have been implemented in order to reduce the antibiotic prescription rate and expectations for antibiotics in RTIs (78). …”
Section: Introductionmentioning
confidence: 99%
“…As these infections are largely viral and self-limiting, antibiotics offer little benefit for these conditions (56). Globally, concerted efforts targeting both clinicians and the public have been implemented in order to reduce the antibiotic prescription rate and expectations for antibiotics in RTIs (78). …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the government of Korea introduced various initiatives to control the use of antibiotics, such as drug utilization review and public reporting of antibiotics for upper respiratory tract infections . In a 2015 survey, 92.6% of hospitals in Korea introduced antimicrobial stewardship programs to control the use of antibiotics, but according to the present study, more efforts are needed to control the use of broad spectrum antibiotics in pediatric patients.…”
Section: Discussionmentioning
confidence: 79%
“…According to the Korea ASP survey in 2015, the number of infectious disease (ID) specialists increased from previous surveys in 2006 and 2012, but the proportion of hospitals operating ASP did not increase; ASP were limited to top-tier general hospitals [8]. The survey concluded that ASP were not proliferating because of the lack of clinical pharmacists and adequate reimbursement from the national health insurance (NHI) system to support ASP [8]. Pharmacists play crucial roles in IPC/ASP; in fact, they can be facilitators or intermediaries at the opinion-gathering stages [9].…”
Section: Introductionmentioning
confidence: 96%
“…The level of antibiotic usage in South Korea (28 defined daily doses [DDD] per 1000 inhabitants per day [DID]) is still much higher than the average for other Organisation for Economic Co-operation and Development (OECD) countries (18 DID) as of 2012 [6,7]. According to the Korea ASP survey in 2015, the number of infectious disease (ID) specialists increased from previous surveys in 2006 and 2012, but the proportion of hospitals operating ASP did not increase; ASP were limited to top-tier general hospitals [8]. The survey concluded that ASP were not proliferating because of the lack of clinical pharmacists and adequate reimbursement from the national health insurance (NHI) system to support ASP [8].…”
Section: Introductionmentioning
confidence: 99%